Choosing Wisely Canada®: Five tests, procedures and treatments to question in Emergency Medicine. (2nd March 2017) - Cheng, Amy H. Y.; Campbell, Sam; Chartier, Lucas B.; Goddard, Tom; Magee, Kirk; McEwen, Jill; Kapur, Atul K.; Holroyd, Brian R.; Upadhye, Suneel; Couperthwaite, Stephanie; Rowe, Brian H.
Abstract: Objectives: Choosing Wisely Canada (CWC) is an initiative to encourage patient-physician discussions about the appropriate, evidence based use of medical tests, procedures and treatments. We present the Canadian Association of Emergency Physicians' (CAEP) top five list of recommendations, and the process undertaken to generate them. Methods: The CAEP Expert Working Group (EWG) generated a candidate list of 52 tests, procedures, and treatments in emergency medicine whose value to care was questioned. This list was distributed to CAEP committee chairs, revised, and then divided and randomly allocated to 107 Canadian emergency physicians (EWG nominated) who voted on each item based on: action-ability, effectiveness, safety, economic burden, and frequency of use. The EWG discussed the items with the highest votes, and generated the recommendations by consensus. Results: The top five CAEP CWC recommendations are: 1) Don't order CT head scans in adults and children who have suffered minor head injuries (unless positive for a validated head injury clinical decision rule); 2) Don't prescribe antibiotics in adults with bronchitis/asthma and children with bronchiolitis; 3) Don't order lumbosacral spinal imaging in patients with non-traumatic low back pain who have no red flags/pathologic indicators; 4) Don't order neck radiographs in patients who have a negative examination using the Canadian C-spine rules; and 5) Don't prescribe antibiotics after incision and drainage of uncomplicated skin abscesses unless extensive cellulitis exists. Conclusions: The CWC recommendations for emergency medicine were selected using a mixed methods approach. This top 5 list was released at the CAEP Conference in June 2015 and should form the basis for future implementation efforts.